Pengaruh Job Crafting terhadap Perilaku Kerja Inovatif Karyawan melalui Keterikatan Kerja sebagai Variabel Mediasi: Studi pada Karyawan PT Pos Indonesia Karesidenan Surakarta - Arsiatul Miftakhil Jannah; Ahyar Yuniawan (Diponegoro Journal of Management, 2026)
The dynamics of the developing workplace and intense industrial competition require every organization to be continuously adaptive, innovative, and to encourage employee initiative. This condition affirms the crucial role of employees in proactively adjusting their jobs, known as job crafting, to achieve alignment between the individual and the organization. However, a research gap exists in previous studies regarding the relationship among job crafting, work engagement, and innovative behavior, where the reported findings remain contradictory. Therefore, this study aims to re-examine and thoroughly analyze the influence of job crafting on employee innovative behavior, and to assess the mediating role of work engagement in this relationship. This quantitative research utilized a survey method on the population of employees of PT POS Indonesia Surakarta Residency. Sampling was conducted using the cluster sampling method, and the collected sample comprised 104 respondents. Data collection was carried out using questionnaires with a Likert scale. The data were analyzed using Structural Equation Modeling (SEM) Partial Least Squares (PLS) via SmartPLS. The research results indicate that: (1) job crafting has a positive and significant effect on employee innovative behavior, (2) job crafting has a positive and significant effect on work engagement, (3) work engagement has a positive and significant effect on innovative work behavior, and (4) job crafting has a positive and significant effect on employee innovative work behavior as mediated by work engagement. These findings provide practical implications for the company to strengthen the role of supervisors as facilitators and providers of positive feedback, creating a conducive and open work environment to enhance employee engagement and encourage innovation.